Novel molecular imprinted polymers over magnetic mesoporous silica microspheres for selective and efficient determination of protocatechuic acid in Syzygium aromaticum. (1st July 2015) - Xie, Lianwu; Guo, Junfang; Zhang, Yuping; Hu, Yunchu; You, Qingping; Shi, Shuyun
Highlights: Preparation of Fe3 O4 @mSiO2 @MIPs with excellent recognition ability. High surface area of mesoporous material increased binding capacity. The composites combined the advantages of Fe3 O4, mSiO2 and MIPs. Fast, efficient and selective extraction of PCA from complex matrix. Abstract: Improving sites accessibility can increase the binding efficiency of molecular imprinted polymers (MIPs). In this work, we firstly synthesized MIPs over magnetic mesoporous silica microspheres (Fe3 O4 @mSiO2 @MIPs) for the selective recognition of protocatechuic acid (PCA). The resulting Fe3 O4 @mSiO2 @MIPs were characterized by transmission electron microscopy (TEM), Fourier transform infrared spectrometer (FT-IR), thermo-gravimetric analysis (TGA), Brunauer–Emmett–Teller (BET), and vibration sample magnetometer (VSM), and evaluated by adsorption isotherms/kinetics and competitive adsorption. The maximum adsorption capacity of PCA on Fe3 O4 @mSiO2 @MIPs was 17.2 mg/g (2.3 times that on Fe3 O4 @SiO2 @MIPs). In addition, Fe3 O4 @mSiO2 @MIPs showed a short equilibrium time (140 min), rapid magnetic separation (5 s) and high stability (retained 94.4% after six cycles). Subsequently, Fe3 O4 @mSiO2 @MIPs were successfully applied for the selective and efficient determination of PCA (29.3 μg/g) from Syzygium aromaticum . Conclusively, we combined three advantages into Fe3 O4 @mSiO2 @MIPs, namely, Fe3 O4 core for quick separation, mSiO2 layer for enough accessible sites, and surface imprinting MIPs for fast binding and excellent selectivity, to extract PCA from complex systems.